Analysis of the variable factors affecting changes in the blood concentration of cyclosporine before and after transfusion of red blood cell concentrate - Masashi Uchida; Natsumi Hanada; Shingo Yamazaki; Hirokazu Takatsuka; Chiaki Imai; Akari Utsumi; Yuki Shiko; Yohei Kawasaki; Takaaki Suzuki; Itsuko Ishii (BMC, 2022)
Abstract Background The blood concentration of cyclosporine (CyA) is frequently elevated following the transfusion of red blood cell concentrate (RCC) to patients after allogeneic hematopoietic stem cell transplantation (HSCT). The aim of this retrospective study was to identify the variable factors affecting changes in the blood concentration of CyA before and after transfusion of RCC. Methods We enrolled 105 patients (age, 5-66 years) who received both CyA and transfusion after HSCT. The ratio of the measurement after transfusion to the measurement before transfusion was calculated for the hematocrit and blood concentration/dose ratio of CyA (termed the HCT ratio and the CyA ratio, respectively). Results The blood concentration/dose ratio of CyA was increased after transfusion compared with before transfusion (P < 0.001). The HCT ratio was significantly correlated with the CyA ratio (P = 0.23, P < 0.001). The HCT ratio, concomitant medication that could elevate CyA concentration after RCC transfusion, and difference in the alkaline phosphatase level between before and after transfusion (ΔALP) were explanatory variables associated with the variation in the CyA ratio. There was no correlation between the CyA concentration after transfusion and the change in the estimated glomerular filtration rate. Conclusions A change in the blood concentration/dose ratio of CyA was found to be associated with a change in the HCT, concomitant medication that could elevate CyA concentration after RCC transfusion, and ALP levels. If the HCT level rises significantly after RCC transfusion, clinicians and pharmacists should pay attention to changes in the blood CyA concentration.